2023
DOI: 10.1111/aji.13673
|View full text |Cite
|
Sign up to set email alerts
|

Altered profile of plasma phospholipids in woman with recurrent pregnancy loss and recurrent implantation failure treated with lipid emulsion therapy

Abstract: Background: Recurrent Pregnancy Loss (RPL) and Recurrent Implantation Failure (RIF) are highly heterogeneous condition and many of the mechanisms involved still require elucidation. The aim was to analyze the lipidomic profile in plasma of women with RPL and RIF before and after receiving the Lipid Emulsion Therapy (LET) containing 10% fish oil (SMOFlipid ® 20%).Methods: This study included twenty-six women with RPL or RIF from immunological or inflammatory causes, with elevated natural killer cell levels and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Previous studies have suggested that intralipid can be used as an alternative therapy for patients with RIF ( Coulam, 2021 ), which is accompanied by an altered profile of plasma phospholipids, specifically PC, after treatment ( Canella et al , 2023 ). Through in vitro experiments, it was also confirmed that PC supplementation rescues serotonin-suppressed decidualization.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that intralipid can be used as an alternative therapy for patients with RIF ( Coulam, 2021 ), which is accompanied by an altered profile of plasma phospholipids, specifically PC, after treatment ( Canella et al , 2023 ). Through in vitro experiments, it was also confirmed that PC supplementation rescues serotonin-suppressed decidualization.…”
Section: Discussionmentioning
confidence: 99%
“…Intralipid is an intravenous immunomodulatory agent that works by altering the function of immune cells, especially by lowering the activity of NK cells. NK cells play an important role in the immunoregulation of normal pregnancy, but their abnormally high activity is associated with RSA 108,109 . By reducing the activity of NK cells, Intralipid helps to create a more tolerant immune environment, thereby promoting the survival and development of the embryo.…”
Section: Diagnosis and Treatment Of Rsa With A Focus On Immunitymentioning
confidence: 99%
“…Власне, феномен збільшення відсотка CD16позитивних мПК -відносно відомий, і його пов'язують із несприятливим репродуктивним прогнозом. Ще у дослідженнях 90-х років минулого сторіччя зазначалося про збільшення частки CD16 + CD56 dim -клітин та зменшення популяції CD16 -CD56 bright у жінок зі звичним невиношуванням [16,24], з перериванням вагітності після застосування ДРТ [9].…”
Section: результати дослідження та їх обговоренняunclassified